Violent Differences: The Importance of Race in Sexual Assault against Queer Men - Meyer, Doug (University of California Press, 2022)
Despite rising attention to sexual assault and sexual violence, queer men have been largely excluded from the discussion. Violent Differences is the first book of its kind to focus specifically on queer male survivors and to devote particular attention to Black queer men. Whereas previous scholarship on male survivors has emphasized the role of masculinity, Doug Meyer shows that race and sexuality should be regarded as equally foundational as gender. Instead of analyzing sexual assault against queer men in the abstract, this book draws attention to survivors' lived experiences. Meyer examines interview data from sixty queer men who have suffered sexual assault, highlighting their interactions with the police and their encounters with victim blaming. Violent Differences expands approaches to studying sexual assault by considering a new group of survivors and by revealing that race, gender, and sexuality all remain essential for understanding how this violence is experienced